2011
DOI: 10.1007/s10236-011-0426-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of different types of Kuroshio intrusion into the South China Sea

Abstract: Kuroshio intrusion into the South China Sea (SCS) has different forms. In this study, a Kuroshio SCS Index (KSI) is defined using the integral of geostrophic vorticity from 118°to 121°E and from 19°to 23°N. Three typical paths (the looping path, the leaking path, and the leaping path) were identified based on the KSI derived from the weekly satellite Absolute Dynamic Topography from 1993 to 2008. The KSI has a near normal distribution. Using ±1 standard deviation (σ) as the thresholds, the leaking path is the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
97
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 27 publications
(36 reference statements)
8
97
0
1
Order By: Relevance
“…1, the Kuroshio intruding the SCS through the LUS has been distinguished by three types as the looping path, the leaking path, and the leaping path, according to Nan et al (2011a). All three results show the looping path in winter, the leaping path in summer, and the leaking path in fall, which is well consistent with the model results shown by Wu and Chiang (2007).…”
Section: The Configurations Of Mosupporting
confidence: 82%
See 1 more Smart Citation
“…1, the Kuroshio intruding the SCS through the LUS has been distinguished by three types as the looping path, the leaking path, and the leaping path, according to Nan et al (2011a). All three results show the looping path in winter, the leaping path in summer, and the leaking path in fall, which is well consistent with the model results shown by Wu and Chiang (2007).…”
Section: The Configurations Of Mosupporting
confidence: 82%
“…As pointed out in Hu et al (2000), there were four main features of the Kuroshio intrusion as follows: a direct branch from the Kuroshio (Williamson, 1970;Fang et al, 1996;Chern and Wang, 1998;Qu et al, 2000), a form of loop (Zhang et al, 1995;Liu et al, 1996;Farris and Wimbush, 1996), a form of extension (Hu et al, 1999), and a form of ring (Li et al, 1998a, b) at present. Nan et al (2015) reviewed and summarized the Kuroshio intruding processes from observed data, numerical experiments, and theoretical analyses, and concluded that there were three typical paths of the Kuroshio intruding the SCS, the looping path, the leaking path, and the leaping path, which could be distinguished quantitatively by a Kuroshio SCS Index (Nan et al, 2011a) derived from the integral of geostrophic vorticity southwest of Taiwan. The three paths can change from one to another over several weeks.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, by using AVHRR SST and drifters data, Farris and Wimbush (1996) and Centurioni et al (2004) found that the intrusion of the Kuroshio water into the NESCS occurred most frequently during October and January, and Nan et al (2011b) also pointed out that the Kuroshio intrusion is stronger in winter by using satellite ADT and HYCOM global analysis data. The time of enhanced Kuroshio intrusion is coincident with the period when the AE southwest of the Taiwan is often observed.…”
Section: Forcing Mechanism Inferred From Energy Analysismentioning
confidence: 99%
“…Yuan et al (2006) demonstrated that the anticyclonic intrusion of the Kuroshio is a transient phenomenon rather than a persistent circulation pattern in the Luzon Strait. Nan et al (2011a) defi ned the Kuroshio SCS Index for the fi rst time to quantitatively distinguish the Kuroshio intrusion as three main types: looping, leaking and leaping using altimetry data and HYCOM model results. At the present time, arguments are unresolved regarding how the Kuroshio intrudes into the SCS and what mechanisms control the variability of intrusion patterns.…”
Section: Introductionmentioning
confidence: 99%